A Capacity for Ambiguity?: The Barth-Brunner Debate Revisited - Hart, Trevor A. (Tyndale bulletin, 1993)
This essay seeks to reconsider the debate between Karl Barth and Emil Brunner concerning the relationship between the nature and grace. The first section considers the immediate political and social context for the debate in 1930s Germany, and suggests that only when this Sitz im Leben is taken into account can the urgent tone of Barth's denunciation of Brunner be properly appreciated. Subsequent sections identify the key issues of dispute between the two, especially Brunner's insistent differentiation between a 'formal' and 'material' image of God in humans, and his affirmation of the need for a 'point of contact' for grace in human nature as created and fallen. The essay concludes by exploring an ambiguity in the central term Offenbarungsmächtigkeit, and suggests that there is a way of interpreting this term which satisfies Barth's theological concerns, and which he himself cannot avoid conceding the validity of.